Efect of frequent bushfre on water supply reliability in Thomson Catchment, Victoria, Australia - Khastagi, Anirban; Hossain, Iqbal; Rahmat, Siti Nazahiyah (Springer, 2023)
Melbourne’s water supply is dependent on forested catchments; consequently, frequent occurrence of fre events in these catchments will have detrimental efects on water supply reliability of Melbourne. This study analyses the efect of frequent bushfre events to estimate the reduction in the water yield after a major bushfre event in the Thomson reservoir, which is the largest reservoir supplying water to Melbourne. The Forest Fire Danger Index (FFDI) which is a measure of fre behaviour was used to carry out fre frequency analysis to estimate the frequency of occurrence of a bushfre with certain severity in the catchment area. Seven hypothetical scenarios were adopted to estimate the total water yield in 2010 after the 1939 bushfres considering the presence of manifold species in diferent parts of the Thomson catchment; subsequently, reduction in water yield was calculated for the catchment if a certain percentage of the catchment was burnt once every 10 years after 2010. If 10% of the Ash is burnt every 10 years, the percentage reduction in total water yield varies from 12.2 to 13.9% in 2050 for all seven scenarios considered in the analysis; similarly, the percentage reductions in water yield only from Ash species varies from 21.2 to 23.1% in 2050, if 10% of the Ash is burnt every 10 years. It is expected that improved cognizance of the efect of extreme bushfre events on water yield of Thomson catchment due to frequent bushfre events based on the fndings from the existing study will facilitate the adequate preparedness for risks associated with frequent bushfre events in Victoria’s water supply catchments.